2017
DOI: 10.1016/j.resconrec.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle environmental and economic performance of biochar compared with activated carbon: A meta-analysis

Abstract: As the commercial production and distribution of biochar continues to grow internationally, and its applications diversifying from its early uses as soil amendment, it is important to study the environmental impacts and economic performance of biochar in comparison to activated carbon in order to assess its value. The goal of the study was to assess, through a meta-analysis, the environmental and economic performance of biochar in comparison to activated carbon under an equivalent functional unit to adsorb hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(123 citation statements)
references
References 77 publications
(93 reference statements)
1
122
0
Order By: Relevance
“…The production of 1 kg of activated carbon requires 97 MJ of energy (high activation temperature above 500 °C) and results in 6.6 kg carbon dioxide equivalent emission in the atmosphere. [15] Thus, it is necessary to develop effective and inexpensive new technologies to remove organics from water sources.…”
Section: Doi: 101002/adma201907932mentioning
confidence: 99%
See 1 more Smart Citation
“…The production of 1 kg of activated carbon requires 97 MJ of energy (high activation temperature above 500 °C) and results in 6.6 kg carbon dioxide equivalent emission in the atmosphere. [15] Thus, it is necessary to develop effective and inexpensive new technologies to remove organics from water sources.…”
Section: Doi: 101002/adma201907932mentioning
confidence: 99%
“…Although activated carbon is a well‑known adsorbent for the removal of organic pollutants from water, its production is no longer considered sustainable due to high‑energy demand and greenhouse emissions. The production of 1 kg of activated carbon requires 97 MJ of energy (high activation temperature above 500 °C) and results in 6.6 kg carbon dioxide equivalent emission in the atmosphere . Thus, it is necessary to develop effective and inexpensive new technologies to remove organics from water sources.…”
mentioning
confidence: 99%
“…Biochar costs vary widely, depending on the feedstock, transport, pyrolysis operation, and other factors, but are estimated to range from $350 to $18 000 per metric ton. 130,131 The current cost of biochar is significant compared to construction sand, which is typically used as biofilter media and cost about $8.6 per metric ton in 2015. 132 However, the incremental cost of adding biochar may be worthwhile when also considering its water quality benefits.…”
Section: Social and Economic Considerationsmentioning
confidence: 99%
“…There are only few studies on LCA of the AC production process. Alhashimi and Aktas [26] analyzed environmental impact for biochar comparing with AC by LCA methodology. The study reported that average Greenhouse Gases (GHGs) emissions were calculated to be -0.9 kg CO 2 -eq.…”
Section: Introductionmentioning
confidence: 99%